Pixelating Familiar People in the Media: Should Masking Be Taken at Face Value? - Jelle Demanet; Kristof Dhont; Lies Notebaert; Sven Pattyn; André Vandierendonck (Psychologica Belgica, 2007)
This study questions the effectiveness of masking faces by means of pixelation on television or in newspapers. Previous studies have shown that masking just the face leads to unacceptably high recognition levels, making it likely that participants also use other cues for recognition, such as hairstyle or clothes. In the current study we investigate this possibility by means of an identification task in which participants had to identify (partially) masked images of familiar people. To demonstrate that non-facial cues become increasingly important for recognition as faces are masked more strongly, we manipulated the size of the masked area and the degree of pixelation. Confirming our expectations, increasing the size of masked area or its level of deterioration led to lower recognition rates. More importantly, also an interaction effect between the two variables emerged, showing that additional visual information partly compensates the downswing in recognition when masking becomes stronger. Although in some conditions low recognition rates were found, masking was never a hundred percent effective, making it clear that the media should approach this issue with care. Implications of our findings and future directions are considered.